Arranjos produtivos locais no Piauí: enfoque institucional e identificação - Francisco Prancacio Araújo de Carvalho; Francisco de Assis Veloso Filho; Fernanda Rocha Veras e Silva; Ricardo Alaggio Ribeiro (Informe Econômico (UFPI), 2022)
Não consta.